Literacy In Storytelling Model Teacher With Learning In Primary Circuit City Bandung - Cherawati Cherawati; Bachrudin Musthafa; Isah Cahyani (International Journal of Science and Applied Science: Conference Series, 2019)
The research was carried out based on the development of literacy in elementary school movement. Entering the 21st century, learning literacy has the main objective to provide an opportunity or an opportunity for students to develop themself as a competent communicator in the context of multiliteracy, multicultural and multimedia through its multi-intelligence empowerment. Learning literacy in the elementary curriculum subjects entered in the Indonesian language and literature. In line with this fact, the initial effort should be done to realize the literacy learning is to improve the quality of teachers. Through improving the quality of teachers, teachers are able to develop the quality of learning they have implemented. Improved quality of learning on improving the quality of graduates. The circuit model of learning is a learning model that maximizes empowering thoughts and feelings with the addition pattern and repetition. This study aims to describe: (1) determine the profile of literacy storytelling teacher in elementary school, (2) determine the design of storytelling teachers with models of circuit learning to cultivate the character of students in elementary schools, (3) determine the structure or system presenting fairy tales that can attract students in elementary schools, (4) evaluate the response of students in literacy storytelling teacher at the elementary school. This study used a qualitative approach with the case study method. This research subject is an elementary school teacher in Bandung. The data source of research is: (1) a written source, (2) oral sources, (3) the documents, and (4) recording. Data collection techniques are observation, interviews, and documentation. The process of data analysis research conducted with a qualitative descriptive technique. The results of the study as follows. (1) primary school teachers who have implemented literacy Bandung storytelling, (2) increasing the effectiveness of teachers using circuit models of learning, and (3) increasing the quality of primary school education in the city of Bandung.